Kinetics of catalytic oxidation of carbon monoxide over CuMnAgOx catalyst. (June 2017) - Dey, Subhashish; Dhal, Ganesh Chandra; Mohan, Devendra; Prasad, Ram
Graphical abstract: Abstract: The CuMnAgOx catalyst was prepared by the deposition-precipitation method and followed by calcination at 300 °C, which showed excellent activity and stability for carbon monoxide (CO) oxidation at low temperature. This paper describes the kinetics of catalytic air oxidation of CO over the CuMnAgOx catalyst and their kinetics data were collected in a plug flow tubular reactor. The data were collected under the following reaction conditions: 100 mg catalyst, 2.5% CO in air, total flow rate maintained 60 ml/min and temperature range 25–30 °C. The CO oxidation followed in a different reaction mechanism at a broad range of experimental temperature. A better tool for measuring the performance of CuMnAgOx catalyst for CO oxidation is the activation energy for the process and it's used for the modeling and design of the catalytic converter. The data were fitted into the power law rate equation. The frequency factor and activation energy were found to be 2.7790 × 10 5 (g mol)/(gcat h) and 16.977 kJ/g mol, respectively.